An assessment of health, social, communication, and daily living skills of adults with Down syndrome. Issue 6 (25th April 2018) - Matthews, Theodora J.; Allain, Dawn C.; Matthews, Anne L.; Mitchell, Anna; Santoro, Stephanie L.; Cohen, Leslie
Abstract : Adults with Down syndrome (DS) are surviving longer, yet data delineating life skills are lacking. As providers are encouraged to provide a "balanced" description of DS to family members/caregivers, more quantitative data are required to accurately describe the abilities and potential of adults with DS. This study assessed health, social, communication, and daily living skills of adults with DS to describe the range of abilities and to show how increasing age contributes to functional abilities. Caregivers of an adult with DS 20 years of age or older participated in an online questionnaire. Descriptive statistics and scores from scales assessed relationships between the number of health issues reported and functional abilities, and how the abilities changed as age increased. Of 188 participants, 157 completed the survey with partial results included. Communication, independence, and social activity scores were compared to the number of congenital and non‐congenital health issues reported. Linear regression results showed those with more health issues were significantly less likely to be independent and social. However, only current health issues affected communication skills. No significant correlation occurred between the number of congenital abnormalities and scores for independence/life skills as an adult. T ‐test by age group found decreasing abilities after 40 years of age. In conclusion, quantitative data and information from this study is beneficial for providers in order to describe the potential for an individual with DS and to assist caregivers to plan accordingly for the future of their adult with DS.